Maritime Habitus and Learning Ethos Among Bajo Youth: Negotiating Scholling and Sea Life in Kawite-Wite - Rosmawati Taherong; Maria Ulfa; Erviana Antasari; Mardiana Mardiana (Sakura Digital Nusantara, 2026)
Purpose: This study aims to analyze how maritime habitus shapes the learning ethos of Bajo youth in Kawite-Wite Village, Muna Islands, Southeast Sulawesi, by addressing a research gap in coastal education studies that have largely emphasized access, participation, and dropout, while paying limited attention to maritime culture as both educational capital and structural challenge. Methods: This study employed a descriptive qualitative approach within a critical sociology of education paradigm using a phenomenological-sociological design. Data were collected through participant observation, semi-structured in-depth interviews, focus group discussions, and documentation involving 24 informants, consisting of 16 Bajo youth aged 13-18 years and 8 supporting informants, including teachers, a school principal, fishermen parents, a senior fisherman, a Bajo community figure, and a local education observer. Data were analyzed interactively through data condensation, data display, and conclusion drawing/verification. Findings: The findings reveal three central patterns. First, maritime habitus functions as cultural capital through hard work, resilience, solidarity, responsibility, independence, and collective discipline. Second, it produces educational tension through seasonal absenteeism, fatigue, family labor demands, and the risk of school dropout. Third, Bajo youth construct a hybrid future orientation by negotiating their roles as students and children of fishing families. Research Implications: The study implies that coastal education should be culturally responsive, flexible, and connected to maritime life. Originality: This study advances the concept of maritime habitus as an analytical lens for understanding learning ethos as a negotiation between the school field and the sea field.